Quantum Chromodynamic - Piotr Szadkowski, Zbigniew (IntechOpen, 2021)
Quantum chromodynamics is a quantum field theory that describes strong interactions between quarks and gluons. It is the SU(3) gauge theory of the current Standard Model for elementary particles and forces. The book contains several chapters on such topics as quark mixing, the double pole method, the inter-nucleon up-to-down quark bond and its implications for nuclear binding, and more. Readers should be fluent in advanced mathematics and quantum physics. Knowledge of quantum electrodynamics is welcome.